Tradisi Risywah (Suap Menyuap) dalam Pemilihan Kepala Desa dalam Tinjauan Saddu Adz-Dzariah (Studi terhadap Fatwa MUI NO. VI Tahun 2000) - Azyyati, Salwa (CV. Ridwan Publisher, 2021)
This article focuses on Islamic Law related to Risywah using the Saddu Adz-dzariah concept. The phenomenon of Risywah in Jombang society is still wrong in understanding the contextual Risywah and considers it to be a gift, causing anxiety and fear as a result, enmity and intolerance arise. This study aims to mediate differences in public opinion regarding Risywah because some are of the opinion that it is haram and some say it is halal or permissible. To respond to this, it is necessary to know the factors that encourage people to accept these gifts and analyze the Risywah Tradition with the Saddu Adz-Dzar'ah Perspective, to get clear answers about the law of the practice of the Risywah tradition. The method used in this research is descriptive qualitative analysis method, with the type of field research (field research). Using interview and observation techniques in collecting data. The results of the study: First, that the underlying factors encourage people to accept the gift, namely because of an urgent need that cannot be postponed, if it is postponed it will cause great difficulties (Masyaqqah) for low-income people, Second, that the underlying factors encourage people to accept the gift, namely because of weak Iman (Dha'ful Iman), and do not feel that the act is being watched by Allah SWT either the person doing it or the person receiving it ('Adamu al muraqabatillah), and greedy in the sense that the person who does it does not believe that Allah SWT is the one who determines everything that happens